Analysis of the coupled electro-osmotic and mechanical consolidation in clayey soils. Issue 3 (6th June 2018) - Gargano, Sara; Lirer, Stefania; Flora, Alessandro
Abstract : Electrokinetic (EK) treatment is a possible attractive way to speed up the consolidation of fine-grained dredged sediments. The effectiveness of this method depends on the complex physical–chemical interaction between soil particles, interstitial fluid and pollutants. This paper presents the experimental laboratory results obtained by inducing mechanical and EK consolidation in a fine-grained dredged material. Then, a finite-difference numerical code implemented by the authors able to solve the large and small strain consolidation equations (Lassec1), including the electro-osmotic flow, is described along with the theoretical simplifications adopted and the calibration procedure required. The experimental results have been numerically simulated, showing the ability of Lassec1 to reproduce the coupled mechanical and electrical consolidation processes, highlighting that under very low stress levels it is necessary to take into account the highly non-linear soil behaviour, and thus the large strain theory is needed to obtain a reliable prediction of the consolidation process. With this aim, special laboratory devices are necessary for a good calibration of the permeability function and of the stress–strain relationship at very low stress levels.